Impact of Global Managerial Strategies on 4.0 Industrial Revolutions - Islam, Rabiul; Yatiban, Aminurraasyid; Othman, Muhammad Fuad; Mat, Bakri (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper was to address the impact of global managerial strategies on 4.0 industrial revolutions. The engagement of technology and factory in industrial revolution 4.0 become a crucial part of new ways doing business globally. Data for this study were obtained from existing literatures on industrial revolutions. The methodology heavily relied on existing previous literatures on the subject being dealt with. The findings indicate that managers must be wise and brilliant enough to choose what the best way is. Since the revolution in rapidly evolve, it is very important to have a good leadership trait and being dynamic accordingly with the situation. Global managerial strategies would respond to 4.0 industrial revolutions and at the same time looking forward to have a sustainable development. Therefore, it must always be aware and ready to change so that the country does not miss out on the era of the industrial revolution 4.0.